Laying Hen Farming as Agribusiness Potential - Anak Agung Istri Agung Peradnya Dewi; Moh Saifulloh (SOCA: Jurnal Sosial Ekonomi Pertanian, 2024)
This study examined the potential of Quantum GIS (QGIS) as a cutting-edge tool for analyzing and comprehending the spatial dynamics of the livestock industry, particularly in identifying ideal locations for layer chicken farms in Tabanan Regency’s Penebel District. The objective of this study was to identify the characteristics of entrepreneurs who own layer-breeder chicken farms in the Penebel District and analyze the agribusiness prospects of such farms in the same district. Employing a descriptive qualitative analysis approach with an exploratory survey using the QGIS 3.34.5 application. The respondents were selected through purposive sampling. The results indicated that the majority of layer chicken farm owners in Penebel District are middle-aged men (56-65 years old) with high school education and have gathered substantial cash amounting to hundreds of millions. They typically own between 3,001 and 10,000 laying hens. Potential farm owners are concentrated in the villages of Babahan, Senganan, and Jatiluwih. This study aimed to facilitate collaboration between the Tabanan District Government and relevant companies to assist layer farmers in expanding their market share and identifying suitable financial options. Furthermore, this study has the potential to extend the application of GIS technology in the livestock business to other regions undergoing comparable development